Modification of Epoxidized Ricinoleic Acid for Biolubricant Base Oil With Improved Flash and Pour Points - Salimon, Jumat; Salih, Nadia (Asian Journal of Chemistry, 2010)
Low-temperature properties need to be improved before lubricant oils can receive wider recognition as biodegradable base oil. In the present work in order to produce ricinoleic acid based biolubricants with good flash and low pour points, epoxidized ricinoleic acid (ERA) was chemically modified. Epoxidized ricinoleic acid was reacted with various fatty acids in the presence of p-toluenesulfonic acid (PTSA) as a catalyst to give a ring-opened intermediate product. Isobutanol was used to esterify the carboxylic acid hydroxyl groups of the ring-opened products. Some physical properties of each synthesized compound was determined through its pour point, viscocity and flash point values. Furthermore, the chemical structure for each one was confirmed through its FTIR, 1H NMR and 13C NMR spectra.